An?lise de desempenho de sistemas multiportadora utilizando modula??es M-QAM n?o quadradas em canais com ceifamento - Silva, Magna Luzia da (2004)
The Orthogonal Frequency Division Multiplexing (OFDM) technique has been the subject of research in institutions around the world. The use of OFDM has been especially considered in digital transmission systems susceptible to the effects caused by frequency selective fading. Among the applications of this technique, it is possible to highlight the Digital TV standards, such as ISDB-T (Integrated Service of Digital Broadcasting - Terrestrial) adopted in Japan and DVB-T (Digital Video Broadcasting - Terrestrial) adopted in Europe, the Third-generation mobile cellular communication and wireless local area network standards such as IEEE 802-11a and IEEE 802-11g. However, there are some difficulties that limit the use of OFDM. One of the largest of these refers to the need to maintain synchronism between the N oscillators of the transmitter and the receiver of the system due to the orthogonality between the subcarriers. With the development of the digital signal processors it was possible to solve this problem and make feasible the OFDM technique. Another relevant difficulty is the occurrence of high amplitude peaks of the OFDM signal. This happens because this signal has a high relation between its peak power and its average power. In order to reduce costs, the power amplifiers are designed to be high performance, ie operating near saturation point. Thus, the high peaks of the OFDM signal are harvested, introducing non-linear distortion and compromising system performance. The main objective of this work is to investigate the effects of the occurrence of harvesting on the performance of OFDM systems that use non-square M-QAM modulations. Thus, firstly, the generation and detection methods of OFDM signals are presented. Then, the performance of the cross-constellation M-QAM modulations and overlap in the Additive White Gaussian Noise (AWGN) channels is analyzed. Subsequently, the characteristics of the OFDM signal and the reasons that lead to the occurrence of the harvest are presented. Also presented are two models for mowing analysis, as well as the probability of symbol error due to mowing for OFDM systems using non-square M-QAM modulations with cross or superimposed constellation. Finally, the theoretical results obtained are compared with computational simulation.